2019
DOI: 10.12788/jhm.3262
|View full text |Cite
|
Sign up to set email alerts
|

Improving Resident Feedback on Diagnostic Reasoning after Handovers: The LOOP Project

Abstract: Appropriate calibration of clinical reasoning is critical to becoming a competent physician. Lack of follow-up after transitions of care can present a barrier to calibration. This study aimed to implement structured feedback about clinical reasoning for residents performing overnight admissions, measure the frequency of diagnostic changes, and determine how feedback impacts learners’ self-efficacy. Trainees shared feedback via a structured form within their electronic health record’s secure messaging system. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Viewpoint in diagnosis after care transitions was viewed positively and noted to contribute to improving clinical practice and identifying system vulnerabilities. 20 Among German primary care physicians, patient outcome feedback resulted in self-reflection and resolve to improve analytical reasoning and change clinical practice. 21 Consistently relaying patient outcomes to upstream clinicians also eliminates reliance on individual motivations to seek feedback.…”
Section: Interpersonal Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Viewpoint in diagnosis after care transitions was viewed positively and noted to contribute to improving clinical practice and identifying system vulnerabilities. 20 Among German primary care physicians, patient outcome feedback resulted in self-reflection and resolve to improve analytical reasoning and change clinical practice. 21 Consistently relaying patient outcomes to upstream clinicians also eliminates reliance on individual motivations to seek feedback.…”
Section: Interpersonal Barriersmentioning
confidence: 99%
“…One study used an EHR-generated templated feedback form delivered via the EHR's messaging function to determine the effect of structured feedback to resident trainees who admitted patients overnight. 20 After the intervention, residents indicated improved comfort with sharing feedback and self-efficacy in identifying cognitive biases.…”
Section: Using the Ehr To Create Feedback Loopsmentioning
confidence: 99%
“…Studies have suggested that the diagnostic process is one from which much rich learning can be gleaned, but this must be intentional and does not happen without significant institutional investment and individual commitment. 19 These 3 components are related to one another: a just culture is a prerequisite for a reporting culture, which in turn is needed to create learning opportunities for a learning culture. The DEI addresses all 3 of the cultural aspects.…”
Section: The Diagnostic Error Indexmentioning
confidence: 99%
“…Providers and HCOs, often unaware of their patients' ultimate diagnosis-related outcomes, could benefit from measurement of diagnostic performance, which can then contribute to better system-level understanding of the problem and enable improvement through feedback and learning [27][28][29]. Developing and implementing measurement methods that focus on what matters is consistent with LHS approaches [30].…”
Section: Understanding the Multifactorial Context Of Diagnostic Safetymentioning
confidence: 99%